Indian Accents : Brown Voice and Racial Performance in American Television and Film - Dave, Shilpa (Book collections on Project MUSE., 2013)
"The representation of Indian Americans as foreign terrorists and as citizens who speak with an American accent comprise a major plot point in Harold and Kumar Escape From Guantanamo Bay. In American media, South Asians vacillate between being cast as racially foreign while simultaneously being praised as a model minority because they are highly educated, speak English, and can economically succeed in America. In American cinema and television, Shilpa Dave serves how contemporary images of South Asians build upon, modify, and at times diverge from previous stereotypes of Asian Americans as immigrants and model minorities"--